2020
DOI: 10.1088/1748-0221/15/02/p02019
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of a dirty bomb attack in a large metropolitan area: simulate the dispersion of radioactive materials

Abstract: The potential for a radiological or nuclear attack has been widely acknowledged in the last two decades. The use of a dirty bomb by terrorist organizations is considered to be a credible threat for which policymakers and relevant security agencies must prepare. Radioactive materials are stored in thousands of facilities around the world and may not be adequately protected against theft. This article analyzes a hypothetical dirty bomb attack in a large metropolitan area, evaluating the radiation dose to the inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…The number of conceivable radionuclides is very large, and it is not possible to predict which one is suitable for a terroristic attack [11]. In fact, it depends on many factors such as availability, opportunity to steal and manage, easiness to transport, and many other reasons.…”
Section: Radionuclidesmentioning
confidence: 99%
“…The number of conceivable radionuclides is very large, and it is not possible to predict which one is suitable for a terroristic attack [11]. In fact, it depends on many factors such as availability, opportunity to steal and manage, easiness to transport, and many other reasons.…”
Section: Radionuclidesmentioning
confidence: 99%
“…It was found that when changing the explosive amount to 907 kg, while keeping the other simulation parameters constant, the TEDE values were lower than the TEDE values obtained for a smaller explosive of 68 kg. This implies that the higher the explosive power, the higher the dispersion of the radionuclide and consequently the lower the TEDE and the radionuclide ground surface deposition (Bioncotto et al 2020).…”
Section: Resultsmentioning
confidence: 99%
“…• to predict the atmospheric release of radioactive material in the form of particles and dust due to the detonation of a hypothetical improvised nuclear device [20];…”
Section: Analysis Of Advantages/ Disadvantages and Selection Of Hot Spotmentioning
confidence: 99%
“…HotSpot is a hybrid of the well-established Gaussian Plume Model, widely used for initial emergency assessment or safety analysis planning. Virtual source terms are used to model the initial atmospheric distribution of source material following explosion, fire, resuspension, or user-input geometry [20].…”
Section: Description Of the Software The Model Used And The Weather Conditions Selectedmentioning
confidence: 99%